PERAN UN WOMEN DALAM MENDUKUNG KEBIJAKAN EQUAL PAY FIFA SEPAK BOLA WANITA DI INGGRIS - Pradana, Iqbal; Lokmana, Raja Saputra; Hutasoit, Inka Kristin Pranata; Triyanti, Febi (Pusat Penelitian Pemberdayaan Perempuan, Gender, dan Anak UMRAH, 2022)
Football is a popular sport with an incredible number of fans spread all over the world. Everyone can be sure to have basic knowledge about the sport of soccer. This can not be separated from the ability of good publicity and the special appeal of the sport, such as players, football clubs, to its history. Through a survey conducted by FIFA, there were 250 million active football players spread across 200 countries with 3.5 billion fans (Avaz, 2021). In explaining this problem, the type of research methodology used is a qualitative approach. The purpose of this study is to find out the various strategies implemented by UN Women to support FIFA Equal Pay and to know the process of implementing FIFA's Equal Pay policy for female soccer players in England. The results of this study indicate that by cooperating with FIFA, UN Women is trying to raise awareness of gender equality in soccer